Antigen-antibody reaction in solution in capture competition immunoassay for human immunodeficiency virus antibodies. - Nielsen, C M (1989)
In the capture competition immunoassay, undiluted serum was reacted in solution with purified human immunodeficiency virus (HIV) antigen in wells of microtest plates coated with anti-HIV immunoglobulin G antibodies (HIV capture antibodies). HIV antibodies present in the serum being tested combined with the HIV antigen and thus blocked (completely or partially) the fixation of the antigen to the capture layer. Unblocked antigenic activity was measured in subsequent steps by the use of biotinylated anti-HIV immunoglobulin G and peroxidase-conjugated avidin. The assay was evaluated in comparison with indirect enzyme-linked immunosorbent assay and Western (immuno-) blot (WB). A total of 180 serum samples which reacted repeatedly as positive in indirect enzyme-linked immunosorbent assay but negative in WB were found to be negative by the capture competition assay. Of 54 serum samples showing dubious reactions (single p24 bands in WB), 53 were clearly separated into positive or negative reactions, whereas 1 serum sample gave a borderline reaction. It was concluded that a characteristic feature of this kind of inhibition assay is a very low frequency of equivocal results.